Combined use of CSF NfL and CSF TDP‐43 improves diagnostic performance in ALS. Issue 12 (19th November 2019) - Kasai, Takashi; Kojima, Yuta; Ohmichi, Takuma; Tatebe, Harutsugu; Tsuji, Yukiko; Noto, Yu‐ichi; Kitani‐Morii, Fukiko; Shinomoto, Makiko; Allsop, David; Mizuno, Toshiki; Tokuda, Takahiko
Abstract: Objective: To determine the diagnostic and prognostic significance of neurofilament light chain (NfL), TAR DNA‐binding protein 43 (TDP‐43), and total tau (t‐tau) in cerebrospinal fluid (CSF) and plasma of patients with amyotrophic lateral sclerosis (ALS) and to investigate whether the combined use of those biomarker candidates can improve their diagnostic performance. Methods: This was a single–center, prospective, longitudinal study. CSF and plasma samples were collected at the time of enrollment from a discovery cohort of 29 patients with ALS and 29 age–matched controls without neurodegenerative disease. In a validation cohort, there were 46 patients with ALS, and 46 control (not age‐matched) patients with motor weakness resulting from neuromuscular diseases. NfL, TDP‐43, and t‐tau levels in CSF and plasma were measured using ultrasensitive single molecule assay (Simoa) technology. Results: The following findings were reproducibly observed among the discovery and validation cohorts: increased levels of CSF NfL, plasma NfL, and CSF TDP‐43 in ALS compared with control groups; shorter survival associated with higher levels of CSF and plasma NfL. When the CSF NfL and CSF TDP‐43 levels were combined, the areas under the ROC curves (AUC) were slightly improved relative to AUCs for each biomarker alone. Interpretation: CSF and plasma NfL may not only serve as diagnostic biomarkers but also provide a measure of disease progression. CSF TDP‐43 is also useful as a diagnostic biomarker of ALS, but has no prognostic value. The combined use of CSF NfL and CSF TDP‐43 may be a useful biomarker for the diagnosis of ALS.